The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.3109/08880019609030870
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Humoral Cytotoxicity Against Neuroblastoma (NB) Cells in Healthy Persons and Nb Patients

Abstract: A novel cytotoxic mechanism against neuroblastoma (NB) cells based on natural immunoglobulin M serum antibodies is described. The occurrence of these antibodies, which are able to induce complement-mediated cytolysis of NB cells, has been investigated in several age groups of healthy persons and in patients with NB. The cytotoxicity of serum samples has been measured in terms of propidium iodide DNA incorporation using a FACScan. The prevalence of anti-NB 1gM antibodies shows a strong age dependence characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In our previous studies, we discovered the presence of anti‐NB antibodies in sera of healthy individuals including children and adults. ( 12,13 ) These naturally occurring antibodies are of the IgM class and elicit effective killing of human NB cells in vitro by both complement activation and induction of apoptosis. ( 13,14 ) Subsequent in vivo studies in nude rats with human NB xenografts demonstrated the inhibition of tumor growth by treatment with the IgM fraction from healthy adults with a high titer of natural anti‐NB IgM.…”
mentioning
confidence: 99%
“…In our previous studies, we discovered the presence of anti‐NB antibodies in sera of healthy individuals including children and adults. ( 12,13 ) These naturally occurring antibodies are of the IgM class and elicit effective killing of human NB cells in vitro by both complement activation and induction of apoptosis. ( 13,14 ) Subsequent in vivo studies in nude rats with human NB xenografts demonstrated the inhibition of tumor growth by treatment with the IgM fraction from healthy adults with a high titer of natural anti‐NB IgM.…”
mentioning
confidence: 99%